THE EFFECT OF BOARD OF DIRECTOR, BOARD OF COMMISSIONER AND AUDIT COMMITTEE ON VALUE OF FIRM TO ISLAMIC SOCIAL REPORTING AS A MEDIATING VARIABLE - RIKA LIDYAH; AMRI AMIR; SYAHMARDI YACOB; SRI RAHAYU (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
This research aim to analyze the effect of number of Board of Directors, number of Commissioners and audit committee of the company with the Islamic social reporting as mediation variables. This research was conducted on the basic and chemical industrial enterprises registered in the ISSI. The research found that the number of Board of Director, number of Commissioners and audit committee of the value of firm affects. The number of Board of Director of Islamic have effect on social reporting, whereas number of Commissioner and audit committee do not have effect to the Islamic social reporting. Islamic social reporting can mediate all the variables (the number of Commissioner and the Board of Director, the audit committee of the company)